Child privacy rights: A ‘Cinderella’ issue in HIV-prevention research - Ann Elaine Strode (Southern African Journal of HIV Medicine, 2013)
Legal debates regarding child participation in HIV research have tended to focus on issues of informed consent. However, much less attention has been given to privacy; accordingly, we classify this as a ‘Cinderella issue’ that has been excluded from ‘the ball’ (academic debate). Here we argue that privacy issues are as important as consent issues in HIV-prevention research. We describe a child’s right to privacy regarding certain health interventions in South African law, and identify four key norms that flow from the law and that could be applied to HIV-prevention research: (i) children cannot have an expectation of privacy regarding research participation if they have not given independent consent to the study; (ii) children may have an expectation of privacy regarding certain components of the study, such as HIV testing, if they consent independently to such services; (iii) children’s rights to privacy in health research are limited by mandatory reporting obligations; (iv) children’s rights to privacy in HIV-prevention research may be justifiably limited by the concept of the best interests of the child. We conclude with guidelines for researchers on how to implement these principles in HIV-related research studies.